A revised and geo-referenced list of type localities for termites in South America - Constantino, Reginaldo (Zootaxa, 2019)
A revised, geo-referenced, and cross-referenced list of 270 termite type localities in South America is presented. A total of 543 nominal species-group extant taxa are listed, 442 of them valid and 97 synonyms. The type-locality comprising the greatest number of nominal taxa in South America is Kartabo, Guyana (A.E. Emerson study site), with 59 taxa, followed by Cuiabá, Brazil (F. Sivestri), with 34, and Ribeirão Cascalheira, Brazil (Xavantina-Cachimbo Expedition, A.G.A. Mathews) with 26.